Developing â€œReverb Englishâ€ Textbooks for Kindergarten Students: Is It Effective? - Fikra Raushani Khittahira; Peptia Asrining Tyas (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
English is one of the foreign languages taught in Indonesia. It has separated curriculum from other subjects which are taught in primary, secondary, and high schools by using English textbooks. However, English textbooks are limited to be developed in Kindergarten area. Therefore, this research conducted and aimed to develop adequate English textbooks based on Kindergarten syllabus which are annual and semester programs by the school. The researcher took the group A and B learners of Kindergarten students at TK Negeri Pembina 1 Malang year 2021/2022. The researcher involved 70 students as the participants. Research and Development (R&D) was conducted in this research with the ADDIE model. The instruments of the research were observation and interviews both teacher and students. The data analysis was obtained from the expert validation checklist also the transcription of the result from the interview with both teachers and students. Findings indicate that â€œReverb Englishâ€ textbooks are feasible and effective during the English teaching-learning process in the classroom for kindergarten students. It can help them to learn faster by visualizing the pictures and words in the book.